The Anti-Bureaucratic Ghost in China's Bureaucratic Machine. (10th November 2021) - Ding, Iza; Thompson-Brusstar, Michael
Abstract: The Chinese Communist Party's (CCP) ideology, rooted in its foundational struggles, explicitly denounces "bureaucratism" ( guanliaozhuyi ) as an intrinsic ailment of bureaucracy. Yet while the revolutionary Party has blasted bureaucratism, its revolutionary regime has had to find a way to coexist with bureaucracy, which is a requisite for effective governance. An anti-bureaucratic ghost thus dwells in the machinery of China's bureaucratic state. We analyse the CCP's anti-bureaucratism through two steps. First, we perform a historical analysis of the Party's anti-bureaucratic ideology, teasing out its substance and emphasizing its roots in and departures from European Marxism and Leninism. Second, we trace both the continuity and evolution in the Party's anti-bureaucratic rhetoric, taking an interactive approach that combines close reading with computational analysis of the entire corpus of the People's Daily (1947–2020). We find striking endurance as well as subtle shifts in the substance of the CCP's anti-bureaucratic ideology. We show that bureaucratism is an umbrella term that expresses the revolutionary Party's anxiety about losing its popular legitimacy. Yet the substance of the Party's concern evolved from commandism and revisionism under Mao, to corruption and formalism during reform. The Party's ongoing critiques of bureaucratism and formalism unfold in parallel fashion with its efforts to standardize, regularize and institutionalize the state.